A salutogenic program to enhance sense of coherence and quality of life for older people in the community: A feasibility randomized controlled trial and process evaluation. Issue 1 (January 2016) - Tan, Khoon Kiat; Chan, Sally Wai-Chi; Wang, Wenru; Vehviläinen-Julkunen, Katri
Highlights: Salutogenesis-based self-care is an effective primary health promotion approach. Salutogenesis-based self-care program improves sense of coherence and psychological aspect of quality of life. Salutogenesis-based self-care program improves self-care abilities. Engagement with personal and external resources enhances self-care abilities. Abstract: Objective: To determine the feasibility of a salutogenesis-based self-care program on quality of life, sense of coherence, activation and resilience among older community dwellers. Methods: This is a feasibility randomized controlled trial. Sixty-four older community-dwellers were recruited from a Singapore senior activity center and randomly assigned to intervention and control groups. The intervention group attended a 12-week Resource Enhancement and Activation Program. The outcomes were assessed with the Chinese versions of World Health Organization Quality of Life Scale, Sense of Coherence, Patient Activation Measure, and Connor–Davidson Resilience Scale. Process evaluation was conducted using focus groups with the intervention group. Results: At the end of the program, the intervention group showed significant improvement in the Sense of Coherence scale and the psychological subscale of the WHO Quality of Life scale compared with the control group. Three themes emerged from the process evaluation: participation in the program, reflection on the experience, and improving the experience. Conclusion: A salutogenic self-care approach could be a potential health promotion strategy for older people. Practice implications: With improved sense of coherence and psychological aspect of quality of life, older people's self-care ability may improve, leading to better health and better quality of life.